就 那條 發(fā)視頻的 一視頻 提到的 一定理 之證明 饗以諸君

設(shè)
ax3+bx2+cx+d=0
三根
x1,x2,x3
有
ax13+bx12+cx1+d=0
ax23+bx22+cx2+d=0
ax33+bx32+cx3+d=0
即
a(x1-x2)(x12+x1x2+x22)+b(x1-x2)(x1+x2)+c(x1-x2)
=
0
即
a(x12+x1x2+x22)+b(x1+x2)+c=0
同
a(x22+x2x3+x32)+b(x2+x3)+c=0
即
a(x1-x3)(x1+x2+x3)+b(x1-x3)=0
即
a(x1+x2+x3)+b=0
即
x1+x2+x3=-b/a
同
a(x12+x1x3+x32)+b(x1+x3)+c=0
即
a(2(x1+x2+x3)2-3(x1x2+x2x3+x1x3))
+
2b(x1+x2+x3)
+
3c
=
0
即
a(2(-b/a)2-3(x1x2+x2x3+x1x3))
+
2b(-b/a)
+
3c
=
0
即
2b2/a-3a(x1x2+x2x3+x1x3)-2b2/a+3c=0
即
x1x2+x2x3+x1x3=c/a
有
(x1x2+x2x3+x1x3)(x1+x2+x3)
=
x12x2+x1x2x3+x12x3
+
x1x22+x22x3+x1x2x3
+
x1x2x3+x2x32+x1x32
=
x12(x2+x3)
+
x22(x1+x3)
+
x32(x1+x2)
+
3x1x2x3
=
-b/a(x12+x22+x32)-(x13+x23+x33)
+
3x1x2x3
=
c(x1+x2+x3)+3d
/
a
+
3x1x2x3
=
-bc+3ad
/
a2
+
3x1x2x3
=
-bc/a2
即
3x1x2x3=-3d/a
即
x1x2x3=-d/a
得證
ps.
有關(guān)那條
罄竹難書
是那什么
還想立牌坊
骯臟齷齪
腌臜不堪
“秒殺大招”
發(fā)視頻的
無(wú)恥行徑
詳見
與
與
標(biāo)簽: